Open Thoracoabdominal Aortic Procedures following Endovascular Intervention - Melloni, Andrea; Kahlberg, Andrea; Rinaldi, Enrico; Bilman, Victor; Favia, Nicola; Melissano, Germano; Chiesa, Roberto (AORTA, 2022)
Open conversion of thoracoabdominal aortic (TAA) disease after failed attempts of endovascular treatment is increasingly required. The main causes are endoleak, endograft failure, infection, disease progression, or persistent false lumen perfusion in dissected aortas. Mortality and morbidity rates are high, higher than after standard TAA open repair. Therefore, this surgery should be performed only in dedicated centers by experienced teams. Specific perioperative organ protection protocols, as well as surgical techniques, are crucial to guarantee acceptable results.
Keywords: aortic aneurysm; endovascular procedure; endoleak; thoracoabdominal